PENYELESAIAN SENGKETA BISNIS MELALUI PENGADILAN NIAGA - Meita Djohan Oelangan (Law Faculty of Universitas Bandar Lampung, 2019)
ABSTRAK The Commercial Court in the Settlement of Business Disputes Linked to the Principle of Legal Certainty As an Effort to Develop the Indonesian Judicial System at this time still needs to be considered to what extent its authority. From this background the problem that is the subject of the research is how is the Commercial Court's authority in resolving business disputes given the lack of clarity about the object of commercial matters that can be handled by the Commercial Court? The research method used is a normative juridical research method through a legislative approach. With data sources namely secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The collected data is analyzed qualitatively. The results of the research show that the authority of the Commercial Court in addition to bankruptcy and other commerce currently being examined is intellectual property rights namely Industrial Design, Layout Design of Integrated Circuits, Patents, Trademarks and Copyright while business disputes are submitted to the Commercial Court which are not regulated by law The law is a case relating to banking, trade agreements, consumer protection, insurance, corporate, transportation and capital markets. As a suggestion the authority of the Commercial Court should be clearly specified in the category of business cases and constitute the absolute competence of the Commercial Court and the Commercial Court to be established throughout the Capital of the Province.